Society and technological change - Volti, Rudi. (New York, NY : Worth Publishers, 2009)
Synopsis: In the Sixth Edition of Society and Technological Change, Rudi Volti continues to bring both his enthusiasm and expertise to the student. Comprehensive in his discussion of both historical and contemporary technological advance, Volti never fails to explore the societal implications of each technology he presents. The new Sixth Edition has been fully updated to include recent technological innovation in such areas as genetics, communications, terrorism, and medicine. Further, updated photos throughout the book bring Volti's words to life.
Part 6: Tools Of Destruction: -- 14: Weapons and their consequences -- Military technology in the ancient world -- Military technology and the feudal order -- New weapons and the decline of Feudalism -- Gunpowder revolution -- War and the centralized state -- Technological change and naval culture in the era of the battleship -- Weapons and the making of the modern world -- Questions for discussion -- Notes -- 15: How new weapons emerge-and how they may be contained -- Action and reaction -- Social structure and the development of military technologies -- Organizational interests and the air weapon -- Social revolution and the enlargement of war -- Industrial technology in the service of war -- Controlling military technologies -- Historical attempts to limit new weapons -- Successful example of arms control -- Gun control in old Japan -- Control of nuclear weapons -- Deterrence, but no more -- Perils of proliferation -- Technology and terrorism -- Cyberterrorism -- Military technologies in a changing world -- Questions for discussion -- Notes -- Part 7: Shaping And Control Of Technology: -- 16: Technology and its creators: who's in charge of whom? -- Technological determinism -- Technological advance and cultural lag -- Convergence theory -- Experts, expertise, and the shaping of technology -- Engineers and the control of technology -- Work environment of engineers -- Questions for discussion -- Notes -- 17: Organizations and technological change -- Technology as a cause of organizational structure -- Technology as a consequence of organizational structure -- Organizations and new information technologies -- Interorganizational relations and technological development -- Organizational size and technological innovation -- Entrepreneurs and organizations -- Questions for discussion -- Notes -- 18: Governing technology -- Government actions and the shaping of technology -- But is it necessary? -- Government institutions for the guidance of technology -- Processes -- Democratic control of technology -- Challenges of the future -- Questions for discussion -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Technology -- Social aspects; Technological innovations -- Social aspects